1985
DOI: 10.1113/jphysiol.1985.sp015782
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pressure maintenance after haemorrhage in the pregnant rabbit.

Abstract: The changes in arterial blood pressure and cardiac output following rapid removal of 10% of the blood volume have been compared in non‐pregnant and pregnant anaesthetized rabbits close to term (28 or 29 days gestation). Immediately after the end of haemorrhage the fall in arterial pressure was greater in the pregnant group (27.7 vs. 17.8 mmHg), but as recovery proceeded the difference diminished and by the tenth minute the reduction from pre‐haemorrhage levels was similar in pregnant and non‐pregnant rabbits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nevertheless, they noted that after hemorrhage, the pregnant animals exhibited greater hypotension due to a greater fall in TPR and hindquarter resistance; the cardiac output responses were similar (14,15). Further work (13) revealed that the response of the femoral vascular bed to stimulation of the sympathetic nerves was similar between pregnant and nonpregnant rabbits, indirectly implying that the smaller degree of vasconstriction in the femoral bed observed in the present study was due to a smaller increase in sympathetic activity rather than decreased vascular responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they noted that after hemorrhage, the pregnant animals exhibited greater hypotension due to a greater fall in TPR and hindquarter resistance; the cardiac output responses were similar (14,15). Further work (13) revealed that the response of the femoral vascular bed to stimulation of the sympathetic nerves was similar between pregnant and nonpregnant rabbits, indirectly implying that the smaller degree of vasconstriction in the femoral bed observed in the present study was due to a smaller increase in sympathetic activity rather than decreased vascular responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Humphreys and Joels (14) investigated the effect of pregnancy on the hemodynamic response to hemorrhage, but two aspects of their experimental approach markedly reduced the duration, and therefore the study, of the first phase: first, the rabbits were anesthetized, which markedly attenuates reflex increases in sympathetic activity during the initial phase of hemorrhage (19), and second, blood loss proceeded very rapidly. Nevertheless, they noted that after hemorrhage, the pregnant animals exhibited greater hypotension due to a greater fall in TPR and hindquarter resistance; the cardiac output responses were similar (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, pregnant individuals exhibit an increased incidence of orthostatic hypotension 4 and a reduced ability to maintain arterial pressure during hemorrhage 57. Despite the fact that peripartum hemorrhage is a major cause of maternal death 8;9, the mechanisms by which pregnancy causes baroreflex dysfunction remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women are prone to orthostatic hypotension, due to blunted reflex activation of the sympathetic nervous system and inadequate peripheral vasoconstriction (56,122,132). Moreover, in many species, pregnancy interferes with the normal ability to maintain arterial pressure during hemorrhage (26,36,99,152,186). Hemodynamic studies have revealed that in pregnant animals, arterial pressure falls with less blood loss due to both a failure to maintain cardiac output and also inadequate peripheral vasoconstriction (22,36).…”
mentioning
confidence: 99%